Budismo: una ética aplicada = Buddhism : an applied ethics - Seoane, Chus Alonso (Ciencias sociales y religión, 2014)
The seeing of people that we consider free of worldly problem, the Buddhist monks, leading pacific demonstrations against the social injustices and suffering of civilians, it becomes a little shock to our preconceived ideas. The present article is a review of some Buddhists key concepts like karma and interdependence. The review of these Buddhists concepts can help to understand this Pacifism as a political route by a middle way, and also to understand the Buddhist ethics as a way and end in itself.